Abstraction Ratio in the Curve Number Method of Runoff Estimation - Bhattacharya, A K; Patil, Jyoti P (Journal of Agricultural Engineering, 2008)
Abstraction ratio refers to the ratio of initial abstraction to the maximum potential retention from rainfall in a watershed. This ratio is an input parameter in the Curve Number method of runoff estimation. The standard value of this ratio is 0.2, which was worked out by analysis of rainfall and stream gauging data of a large number of watersheds in the USA. The Central Unit for Soil Conservation (Hydrology and Sedimentation), Soil Conservation Division, Ministry of Agriculture, Govt. of India, New Delhi had recommended using two values of this ratio namely, 0.1 and 0.3 depending on watershed wetness and soil type. The above two values were recommended based on the analysis of limited stream gauging data for watersheds in India. In the work reported in this paper, the stream gauging data of 28 watersheds in India and 4 watersheds in the USA were considered to work out the abstraction ratio. The analysis revealed that the abstraction ratio varied from 0.15 to 0.67 with a 28-watershed mean of 0.3 and a 32-watershed mean of 0.2941. It was further found that the abstraction ratio data fitted to a normal distribution at 0.04 probability level with a mean of 0.2941 and a standard deviation of 0.1019. The analysis results suggest the possibility of adopting a single value of abstraction ratio as 0.3 for small agricultural watersheds in India.